Menggugat UU Cipta Kerja: Perlindungan Hak Pekerja Kontrak dalam Sistem Outsourcing - Ucok Charles Kairup; Hulman Panjaitan; Gindo L Tobing (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
The Job Creation Law, first introduced in 2020, has sparked significant controversy, prompting widespread protests across Indonesia. Although the Constitutional Court ruled the law conditionally unconstitutional and demanded changes, the 2023 revisions have continued to attract criticism for inadequately addressing workers' grievances. This article evaluates the constitutionality of the Job Creation Law, focusing on the rights of contract workers within the outsourcing system. Through a juridical analysis of two precedent cases and the new Job Creation Law, this article examines the potential success of the petitioners' lawsuits. The conclusion indicates that despite some improvements, the law still contains significant weaknesses that need to be addressed to effectively protect workers' rights.